(3GdcGaj ef GdTGajs - (3Uaj GdOjf eMehO Hf eMeO GdCehj GdeYQha HGdYQGbj GdUhajs; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3BNQgG (B:s
(3HGH GdML s
(3GdfSNI HgG MhGTs
(3TQM GdeSfO ef MOjK GdTGaYjs
(3JHUQI GdYfhGf (B:s
(3JgPjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
Keywords: (3GdMOjK h GdeUWdMs